The oldest monasteries in southern Poland. Selected research problems = Najstarsze klasztory Polski południowej. Wybrane problemy badawcze - Gorazd-Dziuban, Paulina (Przegla̜d religioznawczy, 2020)
Along with the development of Christianity in Poland, there was a need to deepen and maintain it, which is why funded monasteries began to play such an important role. The complexes from the very beginning focused the attention of researchers not only from a social, geographical or religious point of view, but above all archaeological and architectural. Therefore, this work will address emerging and still experiencing problems in researching the oldest conventual assumptions in southern Poland. To this day, many issues focusing on monasteries need to be analyzed in terms of timeliness and possible solutions. Attention should also be paid to the complexity of the problems of medieval convents, as their specificity requires a different development of research, conducting work and analyzing the results. That is why it is so important to proper approach the topic and eliminate or, if possible, reduce the problems that at various stages of operation can significantly hinder research processes.